Deoxyshikonin Inhibits Viability and Glycolysis by Suppressing the Akt/mTOR Pathway in Acute Myeloid Leukemia Cells - Wu, Huijuan; Zhao, Hongmian; Chen, Li (Frontiers in Oncology, 2020)
Deoxyshikonin was reported to exhibit an anti-tumor effect in colorectal cancer. However, no studies are available to illustrate the effect of deoxyshikonin on acute myeloid leukemia (AML). The effects of deoxyshikonin on viability, apoptosis, caspase-3/7 activity, and cytochrome (Cyt) C expression were evaluated by Cell Counting Kit-8 assay, flow cytometry analysis, caspase-3/7 activity assay, and western blot analysis, respectively. Glucose consumption and lactate production were measured to determine the glycolysis level. The expression of pyruvate kinase M2 (PKM2) was detected by quantitative real-time polymerase chain reaction and western blot analysis. The results showed that deoxyshikonin inhibited cell viability and increased the apoptotic rate, the caspase-3/7 activity, and the Cyt C protein level in AML cells in a dose-dependent manner. Additionally, deoxyshikonin concentration-dependently decreased glucose consumption, lactate production, and PKM2 expression in AML cells. Deoxyshikonin inactivated the protein kinase B (Akt)/mammalian target of the rapamycin (mTOR) pathway. The activation of the Akt/mTOR pathway reversed the effects of deoxyshikonin on viability, apoptosis, and glycolysis in AML cells. In conclusion, deoxyshikonin dampened the viability and the glycolysis of AML cells by suppressing PKM2 via inactivation of the Akt/mTOR signaling.